Answer:
x = 6
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Algebra I
Explanation:
Step 1: Define Equation
2(x + 2x) = 36
Step 2: Solve for x
- Combine like terms: 2(3x) = 36
- Divide both sides by 2: 3x = 18
- Divide both sides by 3: x = 6
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 2(6 + 2(6)) = 36
- Multiply: 2(6 + 12) = 36
- Add: 2(18) = 36
- Multiply: 36 = 36
Here we see that 36 does indeed equal 36.
∴ x = 6 is the solution to the equation.